2022
DOI: 10.2196/36966
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Impact of Daily News Exposure During the COVID-19 Pandemic: Ecological Momentary Assessment Study

Abstract: Background Consumption of distressing news media, which substantially increased during the COVID-19 pandemic, has demonstrable negative effects on mental health. Objective This study examines the proximal impact of daily exposure to news about COVID-19 on mental health in the first year of the pandemic. Methods A sample of 546 college students completed daily ecological momentary assessments (EMAs) for 8 wee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…Meanwhile, those who trusted newspapers the most had decreased odds of depression and GAD. While consumption of distressing news during the COVID-19 pandemic was shown to have negative effects on mental health, 17 in our study the type of media people trusted was differentially associated with mental health symptoms. This is however not causative and purely an association, and therefore it is difficult to know whether increased news consumption led to increased mental health symptoms, or vice versa.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Meanwhile, those who trusted newspapers the most had decreased odds of depression and GAD. While consumption of distressing news during the COVID-19 pandemic was shown to have negative effects on mental health, 17 in our study the type of media people trusted was differentially associated with mental health symptoms. This is however not causative and purely an association, and therefore it is difficult to know whether increased news consumption led to increased mental health symptoms, or vice versa.…”
Section: Discussioncontrasting
confidence: 45%
“…A survey of college students between April and December 2020 revealed that greater exposure to news regarding COVID-19 was associated with increased worry about the pandemic, which in turn was associated with greater hopelessness and general worry. 17 …”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous studies suggesting a negative relationship between exposure to negative news and psychological health—that is, higher exposure to negative news could lower one's psychological health (Jain, 2021; Jones et al, 2021; Ma et al, 2021). Greater symptom severity of distress, anxiety, and depression was experienced by individuals who reported to have closely followed COVID‐19‐related news and consumed media across different platforms (Kellerman et al, 2022). During the pandemic, the mass media became not only an avenue for informative data but also a conduit for negative information and fake news (Cinelli et al, 2020; Jain, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…By comparing public agenda-setting with media agenda-setting, research has revealed that news media posts tended to focus on describing and analyzing the developments and progress of COVID-19, whereas posts by members of the public tended to express personal feelings and emotions [ 40 ]. Public sentiment has been reported to change in response to media reports about COVID-19, further indicating that the media agenda and the public agenda influence each other [ 41 ].…”
Section: Research Reviewmentioning
confidence: 99%